Analisis Peramalan Ketinggian Gelombang Laut Dengan Periode Ulang Menggunakan Metode Distribusi Weibull (Studi Kasus Pantai Lembasada Kabupaten Donggala) - Setiyawan, Setiyawan; Rusdin, Andi; Adnyani, Niang (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
Lembasada Beach, Donggala regency is the oldest port in central Sulawesi province which the region has a long coastal area that is 400 km. Most of community events in Donggala regency are located in coastal areas. There are several coastal areas in Donggala that potentially damaged by abrasion, one of which is Lembasada Beach. The effect of the frequent occurrence of erosion and abrasion, buildings and areas around the Beach were damaged by large waves and brunt of the waves could get to the land when there is high tide. The aim of this writing is to determine the height of a wave that will be used in planning the coastal protection building. Measurement of wave height is very rare and hard to achieve therefore in this writing the forecasting of wave heights were conducted through modification of wind speed data for 8 years (2006 – 2013) using the Weibull DistributionMethod based on the Return Period. The data used is secondary data obtained from an extract of the NOAA Earth System Writing Laboratory NCEP/NCAR and processed using WRPLOT then get the maximum wind direction. Based on the result of analysis, it was obtained that the significant wave height and a significant maximum wave period in 2007 on the southwest directon is (Hs) = 0,7969m and (T) = 2,6942 seconds. After analyzing the frequency distribution using Weibull method it can be predicted the wave return period occurence, the return period of 2 years =0,208 m, 5 years = 0,213 m, 10 years = 0,218 m, 25 years = 0,225 m, 50 years = 0,230 m, and 100 years = 0,236 m.